Analysis of the ECO Test Results for Vehicles in the Republic of Croatia - Kovačević, Dražen; Maković, Branko; Sumpor, Davor (Promet - Traffic&Transportation, 2007)
The work presents the classification of engines for theECO test requirement at the technical inspection of vehicles.The types of harmful components in the raw emission of internalcombustion engine are listed and described, as well asthe possibilities of their reduction. In accordance with theclassification of engines for the ECO test requirements the allowedvalues of harmful components according to the legallystipulated standards in Croatia are given. The study includedthe number of vehicles that passed the ECO test at technicalinspection in 2004 and these were then statistically processedand analyzed according to the type of vehicle, classification ofcar engines for the ECO test requirements and the year ofproduction.